Exploring EFL Students' Digital Literacy Practices in Navigating Digital Resources for Academic Writing - Muawwal Al As'ary (Majesty Journal, 2026)
Background. The rapid development of digital resources and artificial intelligence (AI) technology has changed the way English as a Foreign Language (EFL) students’ access, evaluate, and utilize information for academic writing. Although digital literacy is increasingly important in higher education, research exploring how EFL students navigate digital resources during the academic writing process is still limited. Purpose. This study aims to explore EFL students' digital literacy practices in navigating digital resources for academic writing. Methods. This study uses a qualitative approach with a case study design involving 15 students of the English Education master's program at one of the universities in Indonesia. Data were collected through semi-structured interviews and document analysis, then analyzed using thematic analysis based on Braun and Clarke's framework. Results. The research findings reveal four main themes, namely accessing digital resources for academic writing, evaluating the credibility of digital sources, utilizing digital resources and AI-based tools in academic writing, and ethical challenges and considerations in the use of digital resources. Students utilize academic databases and AI-based platforms, evaluate the credibility of sources through academic indicators and verification strategies, and use AI as a cognitive and linguistic support in the writing process. However, they also face challenges related to information credibility, the abundance of digital information, technical constraints, and ethical issues in the use of AI. Conclusion: EFL students' digital literacy practices are multidimensional and include technical, cognitive, and ethical dimensions. These findings affirm the importance of integrating digital literacy and AI literacy in academic writing learning to encourage critical, responsible, and effective use of digital technology in higher education.